Shoemakers before industry: notes on two heterodox interpretation - Guedes, Sebastião Neto Ribeiro (Departamento de Economia, 2016)
The article aimed to compare two approaches that sought to characterize and analyze the evolution of manufacturing and shoe manufacturing in the period of transition that preceded the creation of the great capitalist industrial enterprise. This activity was investigated by two authors, different in terms of methodological affiliation and relatively distant in chronological terms. In fact, although John R. Commons joins the Institutional Economy and Eric Hobsbawn in Marxist historiography, both converge on important aspects when investigating shoe manufacturing. In particular when shifting the emphasis from the processes of change within the activity of technology to changes in the market.